2021
DOI: 10.1371/journal.pone.0244924
|View full text |Cite
|
Sign up to set email alerts
|

Community health worker knowledge, attitudes and practices towards COVID-19: Learnings from an online cross-sectional survey using a digital health platform, UpSCALE, in Mozambique

Abstract: Healthcare workers (HCWs) are at the frontline of the Coronavirus Disease 2019 (COVID-19) pandemic response, yet there is a paucity of literature on their knowledge, attitudes and practices (KAP) in relation to the pandemic. Community Health Workers (CHWs) in Mozambique are known locally as agentes polivalentes elementares (APEs). While technical guidance surrounding COVID-19 is available to support APEs, communicating this information has been challenging due to restrictions on travel, face-to-face group meet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 16 publications
2
37
0
1
Order By: Relevance
“…One study limitation is the relatively low survey response rate from PHCWs, something that was in-line with similar studies conducted during the same period (5,(34)(35)(36). This may be partly explained by the idea that some employees who did not work directly with COVID-19 patients perhaps did not believe that the survey was aimed toward them, and thus refrained from responding.…”
Section: Limitations and Strengthsmentioning
confidence: 76%
“…One study limitation is the relatively low survey response rate from PHCWs, something that was in-line with similar studies conducted during the same period (5,(34)(35)(36). This may be partly explained by the idea that some employees who did not work directly with COVID-19 patients perhaps did not believe that the survey was aimed toward them, and thus refrained from responding.…”
Section: Limitations and Strengthsmentioning
confidence: 76%
“…All these studies were reported in 2020 during the COVID 19 outbreak. Two articles were cross‐sectional surveys (Armand et al, 2021 ; Feldman et al, 2021 ), one was a randomized controlled trial (Owolabi et al, 2020 ), one was a news article (Adebayo et al, 2020 ), one was a narrative review from Kenya (Jaguga & Kwobah, 2020 ), two were observational studies (Adebayo et al, 2021 ; Nlemadim et al, 2021 ), two were letters (Balme et al, 2020 ; Moolla et al, 2020 ), one was a commentary (Kamulegeya et al, 2020 ) and the other one was a retrospective and prospective analysis (Moyo & Madziyire, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The review showed the utilization of telemedicine in Zimbabwe, Cameroon, Uganda, South Africa, Nigeria, Mozambique, Tanzania, and Kenya. The most utilized mode of engaging patients was the telephones (P. Adebayo et al, 2020 ; Armand et al, 2021 ; Balme et al, 2020 ; Kamulegeya et al, 2020 ) and (Feldman et al, 2021 ). Two studies made use of the social media platform Whatsapp (Armand et al, 2021 ; Moyo & Madziyire, 2020 ) while some employed virtual platforms and video calls such as Skype (Armand et al, 2021 ; Moolla et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations